Trends in Patch Testing in the Medicare Part B Fee-for-Service Population. Issue 2 (March 2022) - Ravishankar, Adarsh; Freese, Rebecca L.; Parsons, Helen M.; Warshaw, Erin M.; Goldfarb, Noah
Abstract : Background: Patch testing is a vital component of the workup for allergic contact dermatitis. There are limited data on changes of patch testing use among Medicare providers, as well as patch testing reimbursement rates. Objective: The aim of the study was to evaluate trends in the use of patch testing among various Medicare providers and Medicare patch testing reimbursement. Design: A longitudinal analysis of patch testing claims was performed with the Medicare Part B Physician/Supplier Procedure Summary files from 2010 to 2018. The primary outcomes were the total number and change in the number of submitted patch testing services from 2010 to 2018 by 3 provider groups: dermatology physicians, nondermatology physicians, and nonphysician providers. Secondary outcome measures included Medicare reimbursement amounts and changes in reimbursement amounts for patch test services (total and per 1000 enrollees) from 2010 to 2018 for the 3 provider groups, as well as per patch test service. Results: From 2010 to 2018, submitted patch testing services per 1000 enrollees grew by 89.0%. The annual trend estimate for submitted services relative to 2010 was +10.1% (95% confidence interval [CI] = 8.1 to 12.0) for physicians and +34.1% (95% CI = 32.1 to 36.0) for nonphysician providers (physician assistants and nurse practitioners). Among physicians, the annual trend estimate for submitted services was +5.1% (95% CI = −11.3 to 21.5) for dermatologists and +31.40% (95% CI = 15.00 to 47.81) for allergists. Conclusions: Patch testing increased in the US Medicare population from 2010 to 2018, and this increase was largely driven by nonphysician providers and allergists.